Studi Analisis Komparasi Zakat Perusahaan (Corporate Zakat) dalam Perspektif Fikih dan Peraturan Perundangan - Masadah Masadah (Management of Zakat and Waqf Journal (MAZAWA), 2022)
The assessment of researchers on corporate zakat is separated into two, in particular a restricted view and a wide view. The tight view contends that there is no zakat on the organization, in light of the fact that there is no affirmation from the Prophet. This assessment alludes to the clarification of the traditional researchers who expressed that the subject of zakat (muzakki) is by and large just compulsory on a Muslim who is now mukallaf, free, and has abundance in specific sums and conditions. There is no commitment for lawful elements, associations, or organizations to pay zakat. The individuals who are dependent upon mandatory zakat are individuals who work or are representatives of the organization or lawful element. While the subsequent gathering, which alludes to contemporary researchers, expresses that zakat should be deciphered extensively. They contend that organizations have a mandatory zakat. The organization's zakat itself has been obliged in Article 1 number 5 of Law Number 23 of 2011. Indeed, even Baznas as a foundation doled out by the public authority to get and disperse zakat has additionally worked with organizations wishing to give zakat. Subsequently, it is important to explain the genuine place of the organization as a zakat commitment as indicated by fiqh surveys and laws and guidelines.